The Management of Diabetic Retinopathy: - Aamir Ali (Journal of University Medical & Dental College, 2020)
The symptoms of Diabetes were reported, for the first time 3500 years ago. The complaint of polyurea was described in Papyrus Ebers1. The Papyrus Ebers is the oldest preserved medical document which was written in 1500 BC by Egyptians. It was recovered from Luxor, Egypt and is currently kept in the University of Lipzig, Germany. However the term Diabetes was used in the first century by Aretaeus of Cappadocia.